Tibetan zero nominalization - Hill, Nathan (My University, 2019)
Several researchers draw attention to the ability of Tibeto-Burman languages to use nominalized verb forms in finite contexts (Matisoff 1972, Coupe, ed. 2008, DeLancey 2011), but the reverse pattern—morphologically finite forms occurring in nominal contexts—has received less attention. Here I collect a few examples from Classical Tibetan and Old Tibetan texts of affixless verb forms occurring in syntactically nominal contexts.
PUBLISHED